The Druze Women School Principals as Role Models and Generators of Social Change: A Recent Study - Janan Faraj Falah; Yossi Maman (Current Research in Language, Literature and Education Vol. 2, 2021)
The purpose of this preliminary study is to examine the attitudes of Druze women-school principals in relation to their role and its social significance. The research is qualitative, a “case study” of the phenomenon [1]. Thus, in the “Holistic” research approach [2], the researcher is interested in revealing, learning and understanding the internal world of “subjects” from their point of By this approach, the origin of behavior is affected by definitions, beliefs, values and ideologies of the “subjects” [3]. The turn to higher education has modified the Druze woman’s inferior status, the well educated women became distinguished, greatly affect the Druze parents in general in favor of higher education. The main field work is based on in-depth ethnographic structured interviews as a primary source for information, enabling the interviewee to tell her story freely and still being focused on the research questions. The interviews include 5 Druze women school principals to describe their own personal experiences [4].